Pengelolaan Konten Publikasi Desa Wisata: Menciptakan Keunggulan Daya Saing dan Pengelolaan Berkelanjutan - Buchori, Apit; Sulistyo, Agung; Annisa, Rosalina Nur; Mahanani, Sumiyar (Jurnal Manajemen dan Organisasi, 2025)
The adoption of digital technology has a significant impact on tourism management. The results released by the Organization for Economic Co-operation and Development (OECD) explain that tourism management needs to optimize the role of technology. However, many tourism managers have not implemented technology, including the management of publication content. Limited knowledge, lack of HR competency, and financial conditions are obstacles that arise. On the other hand, tourism managers who implement technology also face problems. The creativity of publication content and the ability to evaluate strategies are additional problems. This study aims to investigate the management of publication content in high-achieving tourist villages. This study uses a qualitative method through an interpretive perspective. Several high-achieving tourist villages in the Special Region of Yogyakarta and Central Java were selected as objects in this research. Qualitative analysis using the Miles Huberman method was used in this study. The results of the study explain that tourist villages can attract tourist visits through the creativity of publication content. This study produces findings on publication content management, including the need for the role of internal managers, the ability to choose themes and content ideas, the intensity of posts, the use of appropriate social media, and improving HR capabilities. The findings in this study are expected to be a role model for managing tourist village content as an effort to create sustainable management.